ISLAMIC ECONOMICS: THE CASE OF MALAYSIA - Dato Jamil Bin Osman; Mohamad Abdul Hamid (Universitas Islam Negeri Imam Bonjol Padang, 2006)
Financial systems are important for allocation of resources in a modern economics. Their landscape is determined by the nature of financial intermediation, i.e. how the function of intermediation is performed and who intermediates betwecn suppliers and users of funds. The acquiring and processing economic entities and the financial contracting are common elements in the activities that diffcrentiate financial intermediation from other economic activities Financial and financial institutions play a vital roie as financial intermediation to allocate Islamic non in Islamic Financial economics intermediation based on the principles of Islam has an established historical record and has resources activities made significant contributionsto economics overtime. Islamic financial system is based on a set of contractsand instruments which form the backbone and building blocks for more